The Impact of Linguistic Distance from English on Economic Growth: A Cross-Country Analysis - Ozkok, Zeynep; Malloy, Brandon; Rowe, Amy (International Journal of Economics and Financial Issues, 2022)
Increasing levels of globalization have contributed to English becoming a preferred language of international communication, education and trade. With countries rapidly embedding English into a large variety of curricula, the demand for English as a medium of instruction is ever growing. Using information from the US Foreign Service Institute's Professional Working Proficiency values, we identify seven distinct linguistic distance from English (LDE) categories, and examine the effects of linguistic distance on income and economic growth across 97 countries over the 1980-2018 period. In addition to the direct effects of linguistic distance on incomes and growth, we further explore its impact through the channels of education and trade. Our results demonstrate that linguistic distance from English affects income levels and growth non-linearly across countries- increased distance from English does not necessarily translate into declining levels of income or growth rates. Conversely, we find that, via the trade channel, more distant languages tend to experience positive rates of growth. Controlling for regional effects or the existence of multiple languages of instruction do not alter our findings. Sub-dividing our dataset by national income levels, we show that the largest negative effects on growth are among Upper-Middle-Income countries.